Pertanggungjawaban Komando dalam Pelanggaran Hak Asasi Manusia di Indonesia - Pravidjayanto, Mochammad Rafi; Alfatoni, Muhammad Aqil; Fajrin, Muslihah Yunita (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2024)
Abstract: The ineffectiveness of legal norms in Article 42 paragraphs (1) and (2) of Law Number 26 of 2000, which contains the material of command accountability, has implications for the impunity of gross human rights violators committed by law enforcement officials. This paper aims to find out the principles, problems, and ideal concepts in command accountability, which will then be internationalised in the National Code of Law (KUHP) with the hope that in the future the a quo article can be effective in ensnaring perpetrators of gross human rights violations, through juridical-normative methods with a conceptual approach, and a statute approach. The results of this article are, first, the existence of inequality in subjective elements in Articles 598-599 of the National Criminal Code, which relates to gross human rights, and Article 42 of Law Number 26 of 2000. This has the potential to ensnare the legal subject of citizens who incidentally are not obligors, so that it is more effective to include the element of command accountability in the explanation of the word "everyone" in the National Criminal Code. Second, in the procedural law of human rights courts, there is a recommendation to use reverse proof strictly by focusing on proving the causal relationship between the involvement of military commanders or civilian superiors and their soldiers or subordinates. Standardisation of evidence is also needed so that cases of gross human rights violations can be resolved immediately.Keywords: Command Responsibility; National Criminal Code; Gross Humanitarian Violence. Abstrak: Ketidakefektifan norma hukum dalam Pasal 42 ayat (1) dan (2) Undang-Undang Nomor 26 Tahun 2000 yang memuat materi pertanggungjawaban komando, berimplikasi pada impunitas pelanggar Hak Asasi Manusia berat (HAM berat) yang dilakukan oleh aparat penegak hukum. Tulisan ini bertujuan untuk mengetahui prinsip, problematika, dan konsep ideal dalam pertanggungjawaban komando yang selanjutnya akan di internaslisasikan dalam Kitab Undang-Undang Hukum Nasional (KUHP Nasional) dengan harapan kedepannya pasal a quo tersebut dapat efektif dalam menjerat pelaku pelanggaran HAM berat. Melalui metode yuridis-normatif dengan pendekatan konseptual (conceptual approach), dan pendekatan perundang-undangan (statute approach). Adapun hasil tulisan ini yakni pertama, adanya ketimpangan dalam unsur subjektif dalam Pasal 598-599 KUHP Nasional yang mengatur terkait dengan tindak pidana yang berkaitan dengan HAM berat, dan Pasal 42 Undang-Undang Nomor 26 Tahun 2000. Hal tersebut memiliki potensi dalam menjerat subjek hukum warga negara yang notabene bukan pemangku kewajiban sehingga lebih efektifnya memasukkan unsur pertanggungjawaban komando pada penjelasan kata “setiap orang” dalam KUHP Nasional. Kedua, pada hukum acara pengadilan HAM terdapat rekomendasi menggunakan pembuktian terbalik secara ketat dengan berfokus pada pembuktian hubungan kausal antara keterlibatan komandan militer atau atasan sipil dengan prajurit atau bawahannya. Standarisasi alat bukti juga diperlukan agar kasus pelanggaran HAM berat di dapat segera terselesaikan.Kata Kunci: Pertanggungjawaban Komando; Kitab Undang-Undang Hukum Pidana; Pelanggaran Hak Asasi Manusia Berat.